2004
DOI: 10.1073/pnas.0407450101
|View full text |Cite
|
Sign up to set email alerts
|

The organization of orientation and spatial frequency in primary visual cortex

Abstract: Many studies have demonstrated that the primary visual cortex contains multiple functional maps of visual properties (e.g., ocular dominance, orientation preference, and spatial-frequency preference), but as yet no consistent picture has emerged as to how these maps are related to one another. Three divergent, prior opticalimaging studies of spatial frequency are reanalyzed and critiqued in this article. Evidence is presented that a nonstimulus-specific response biased the interpretation of results in previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 51 publications
1
49
1
Order By: Relevance
“…5). A recent reanalysis of some ISI images suggested that certain cortical structures identified by ISI, like specific spatial frequency domains, tend to align with blood vessels (Sirovich and Uglesich, 2004), but because ISI relies on hemodynamic changes it is not clear whether these structures have a neural or vascular basis. Because flavoprotein autofluorescence is virtually independent of hemodynamics, AFI maps would be able to distinguish whether such correlations between functional structures and blood vessels are artifactual or genuine.…”
Section: Properties Of the Afi Signal: Spatial Resolutionmentioning
confidence: 99%
“…5). A recent reanalysis of some ISI images suggested that certain cortical structures identified by ISI, like specific spatial frequency domains, tend to align with blood vessels (Sirovich and Uglesich, 2004), but because ISI relies on hemodynamic changes it is not clear whether these structures have a neural or vascular basis. Because flavoprotein autofluorescence is virtually independent of hemodynamics, AFI maps would be able to distinguish whether such correlations between functional structures and blood vessels are artifactual or genuine.…”
Section: Properties Of the Afi Signal: Spatial Resolutionmentioning
confidence: 99%
“…An analysis by Sirovich and Uglesich (2004) suggested that SF domains might be artifacts of intrinsic signal imaging and that SF preference does not vary with position along the cortical surface. However, a subsequent study using flavoprotein autofluorescence imaging, a metabolic but nonhemodynamic mapping signal, produced SF maps with statistically similar structure to those of intrinsic signal imaging, suggesting that the variations in SF preference measured optically are likely genuine (Husson et al, 2006).…”
Section: The Spatial Frequency Mapmentioning
confidence: 99%
“…The main aim of this study was to empirically determine the general scope of applicability of these methods to optical images and their limitations thereof. We also tested the resolving power of these methods by applying them to the problem of mapping spatiotemporal frequency preferences across the surface of the primary visual cortex (Basole et al 2003;Bonhoeffer et al 1995;Hubener et al 1997;Issa et al 2000;Khaytin et al 2008;Shoham et al 1997;Sirovich and Uglesich 2004;Xu et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The main aim of this study was to empirically determine the general scope of applicability of these methods to optical images and their limitations thereof. We also tested the resolving power of these methods by applying them to the problem of mapping spatiotemporal frequency preferences across the surface of the primary visual cortex (Basole et al 2003;Bonhoeffer et al 1995;Hubener et al 1997;Issa et al 2000;Khaytin et al 2008;Shoham et al 1997;Sirovich and Uglesich 2004;Xu et al 2007).Optical imaging of intrinsic signals and voltage-sensitive dyes in vivo has made it possible to test models of cortical organization that could not be easily tested earlier (reviewed by Bonhoeffer and Grinvald 1996). For instance, computational modeling of the results of Hubel and Wiesel (1963) suggested a "pinwheel" pattern of arrangement for orientation maps (Braitenberg and Braitenberg 1979).…”
mentioning
confidence: 99%
See 1 more Smart Citation